China and Southeast Asia : global changes and regional challenges - Ho, Khai Leong, 1954-; Gu, Changyong (Gale virtual reference library, 2005)
Investigates the impacts of global changes and regional challenges confronting the contemporary developments of China-ASEAN relations.